The Aedes aegypti RNA interference response against Zika virus in the context of co-infection with dengue and chikungunya viruses - Leggewie, Mayke; Scherer, Christina; Altinli, Mine; Gestuveo, Rommel J.; Sreenu, Vattipally B.; Fuss, Janina; Vazeille, Marie; Mousson, Laurence; Badusche, Marlis; Kohl, Alain; Failloux, Anna-Bella; Schnettler, Esther (PLOS Neglected Tropical Diseases, 2023)
Author summary Zika virus (ZIKV) is a mosquito-borne human-pathogenic arbovirus of the Flaviviridae family, genus Flavivirus. Other arboviruses, including dengue (DENV) or chikungunya (CHIKV) virus, can occur in the same regions as ZIKV and are also transmitted by Aedes aegypti. Notably, it has been shown that these viruses can co-infect this mosquito, andco-transmission occurs. Such processes may add to the serious public health issues already linked to those pathogens. Arbovirus infections in mosquitoes are controlled through an immune response called RNA interference (RNAi). It is however unknown whether immune responses changs when a mosquito is exposed to a co-infection of ZIKV with either DENV or CHIKV. In this study, we provide evidence that ZIKV co-infections with CHIKV or DENV are similarly well controlled by RNAi as single infections. These findings give new insights into the dynamics of arboviral co-infections in mosquito vectors that increase our understanding of co-infection scenarios during arbovirus outbreaks.